Implementasi CMS pada Website Pemasaran Layanan Pengaspalan Jalan dengan Metode Waterfall - Fadhila, Salsa Mutia Putri; Pramudiawardani, Shelly; Asqia, Misna (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The development of information technology encourages business actors, including the construction service sector, to adopt digital media as a more effective marketing tool. CV Satria Abadi, a road paving service company, faces challenges reaching customers because it still relies on conventional marketing strategies, such as direct communication via messages and phone calls. This research aims to develop a marketing website based on the WordPress CMS to improve information accessibility and service professionalism. The system development was carried out using the Waterfall method. This system is expected to help address existing issues by enhancing access to service information and the company's professionalism. The research results show that the developed website successfully meets user needs and enhances the effectiveness of digital promotion for CV Satria Abadi. Further feature development and regular content updates are planned.